TATA KELOLA KETERSEDIAAN AIR BERSIH PDAM WAY SEKAMPUNG DI KABUPATEN PRINGSEWU - Umayasari, Ulfa (Citizen : Jurnal Ilmiah Multidisiplin Indonesia, 2024)
Clean water management is a strategic issue in regional development, including in Pringsewu Regency. This research aims to analyze the clean water management system, identify the main challenges, and formulate strategies for improving clean water services in the region. The research approach uses qualitative methods with data collection techniques through in-depth interviews, field observations and document studies. Data were analyzed using an interactive model with a focus on policy, institutional and community participation aspects. The research results show that clean water management in Pringsewu Regency still faces various obstacles, such as limited infrastructure, low community access to clean water, and lack of optimal coordination between stakeholders. From an institutional perspective, coordination between regional governments, Regional Owned Enterprises (BUMD), and the community needs to be improved to create a sustainable system. The proposed strategy includes strengthening regulations and clean water management policies, increasing infrastructure capacity through sustainable investment, and empowering communities in managing water resources. Technology-based approaches are also recommended to improve the efficiency of distribution systems and water quality monitoring. It is hoped that this research can become a reference in policy making to ensure equal, sustainable and quality access to clean water in Pringsewu Regency.